Effects of feeding flaxseed on performance, carcass trait, and meat fatty acid composition of Guinea pigs (Cavia procellus) under northern Peruvian condition. - Mustafa, A. (2019)
A study was conducted to determine the effects of flaxseed supplementation on performance, carcass traits, and hindleg fatty acid composition of guinea pigs. Sixty male and female weaned guinea pigs (1 month old, five animals/cage) were blocked by sex and bodyweight and randomly fed 0 (control) or 100 g/kg flaxseed concentrate diets (15 g/animal) plus ad libitum fresh alfalfa for 30 days. Results showed that flaxseed supplementation had no influence on animal performance. However, final body weight (P = 0.035), total feed intake (P = 0.019), and body weight gain (P < 0.001) were higher in male than female guinea pigs. Similar results were also observed for carcass composition (i.e., hot, chilled, and reference carcass weights). Inclusion of flaxseed reduced saturated (P < 0.001), mono-unsaturated (P = 0.004), and increased (P < 0.001) polyunsaturated (PUFA) fatty acid concentrations in hindlegs. Concentrations of linolenic acid and n-3 PUFA increased (P < 0.001) by 49.7 and 37.1%, respectively as a result of flaxseed inclusion. It was concluded that feeding flaxseed to guinea pigs at 100 g/kg of the concentrate diets improves meat PUFA concentrations with no adverse effects on performance or carcass composition.